Wykorzystanie funkcji logistycznej i loglogistycznej do modelowania cyklu życia przedsiębiorstwa - Siedlecki, Rafał (Logistic and Loglogistic Function in Modeling Corporate Life Cycle, 2007)
In this article firm's cycle of life is identified. During the firm's cycle of life changes in revenue, assets and value are observed. It seems that logistic and loglogistic function are very important for modeling business cycle in corporate base on revenue, assets and value.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 469-479